Characteristic Functions and Borel Exceptional Values of E-Valued Meromorphic Functions. (6th November 2012) - Wu, Zhaojun; Xuan, Zuxing
Abstract : The main purpose of this paper is to investigate the characteristic functions and Borel exceptional values of E -valued meromorphic functions from the ℂ R = { z : | z | < R },    0 < R ≤ + ∞ to an infinite-dimensional complex Banach space E with a Schauder basis. Results obtained extend the relative results by Xuan, Wu and Yang, Bhoosnurmath, and Pujari.